Determination of the effect of oxidation on attenuation coefficient of (X-ray) by Cu, Zn and their alloys - Fareed M . Mohammed; Raed N. Razooqi; Mahmoud A. Mohammed (Tikrit Journal of Pure Science)
In this paper we study the effect of the oxidation on the values of total attenuation coefficient for the samples (Cu ,Zn and their alloys Brass (70%Cu +30%Zn), (60%Cu+40%Zn)) . The samples thicknesses chosen (0.02-0.1) cm, the Mo-X-ray tube used with the voltages (20-25-30-35) KV, the effect of oxidation on (  , ) were studied by using the graphic relations, where the effect of oxidation at temperature (100 ˚C) and oxidation time (1.5,6) hours on the linear and mass attenuation coefficients are studied .It is concluded that best results were achieved for  (µL , µm) at (100 ˚C) after six hours where (µL) increased by the ratio (7.14%,5.76%,8.62%3.77%)  .6%,7.4%,8.9%,10.43 n at (100) after six hours , where m  mass attenution respectively, while (µm) increased by (7.05%, 5.79%,10.05%,3.55%) respectively by comparing with oxidized samples for time (1.5) hours at voltage 20 KV, it is found a linear relation between the linear and mass attenuation coefficient with the oxidation time. While they are inversely related with increasing X-ray voltages. the effect of oxidation on the structural from of the studied materials was also examined using both the scanning electron microscope and the X-ray diffraction examination.